FEM modeling of rebar corrosion - numerical verification of experimental research = Modelowanie MES korozji zbrojenia - weryfikacja numeryczna badań doświadczalnych - Krykowski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the experimental verification of concrete cover splitting time theory based on the multicomponent media approach and FEM. The results of computer analysis are compared with the experiment presented in the work of Youping Liu. The solid model of the structure analyzed in the paper has been made. The problem has been analyzed by using the program for the elastic plastic analysis with distortions by using FEM.
Keywords: korozja; teoria plastyczności; metoda elementów skończonych (MES); korozja zbrojenia; corrosion; theory of plasticity; FEM; reinforced concrete degradation